High rates of antibodies against Toscana and Sicilian phleboviruses in common quail Coturnix coturnix birds - Ayhan, Nazli; Rodríguez-Teijeiro, José Domingo; López-Roig, Marc; Vinyoles, Dolors; Ferreres, Josep Anton; Monastiri, Abir; Charrel, Remi; Serra-Cobo, Jordi (Frontiers in Microbiology, 2023)
Birds are involved natural cycle of a number of vector-borne viruses in both sylvatic and rural/urban areas. Toscana (TOSV) and Sicilian (SFSV) phleboviruses are sandfly-borne viruses in the genus Phlebovirus that can cause diseases in human. However, there is limited information on the role of the birds in sandfly-borne phleboviruses natural cycle and reservoirs of these viruses remain unknown. In this study, we analyzed Common Quail (Coturnix coturnix) sera from Spain to identify the seroprevalence of these two phleboviruses. We tested respectively 106 and 110 quail serum against TOSV and SFSV from 2018, 2019 and 2021 from two localities in northern Spain with using virus neutralization test. As a result, we identified high neutralizing antibody rates for SFSV (45.45%) and TOSV (42.45%) with yearly fluctuation. This is the first identification of SFSV and TOSV neutralizing antibodies in wild birds. High seroprevalence rates of TOSV and SFSV in quail birds raises the question whether birds have a role as amplifying hosts in the natural cycle of phleboviruses.